PENGARUH PEKEMBANGAN TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) TERHADAP AKADEMIK SISWA SMK NEGERI 2 PADANG TAHUN AJARAN 2025/2026 - Selva Roza NST; Linda Fitria; Indra Wijaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of Artificial Intelligence (AI) technology development on the academic achievement of Grade X, XI, and XII students at SMK Negeri 2 Padang in the academic year 2025/2026. This research employed a quantitative approach with a correlational method. The sampling technique used was simple random sampling. The research sample consisted of 315 students from a total population of 1488 students. The data collection instrument was a Likert scale questionnaire. Data analysis was conducted using Microsoft Excel 2016. Based on the results of the study, it was found that the value of t count was greater than ttable at the significance level of α = 0.05, therefore the hypothesis was accepted. This indicates that there is a significant influence of Artificial Intelligence (AI) technology development on students’ academic achievement at SMK Negeri 2 Padang. The coefficient of determination analysis shows that AI technology development contributes 30,5% to students’ academic achievement. Thus, the better the utilization of AI technology by students, the better their academic performance, particularly in terms of understanding learning materials, timely task completion, and improvement of learning outcomes.